Accommodation of helium in PuO2±x and the role of americium. Issue 14 (23rd March 2022) - Neilson, William D.; Steele, Helen; Kaltsoyannis, Nikolas; Murphy, Samuel T.
Abstract : The high alpha-activity of plutonium dioxide (PuO2 ) results in significant ingrowth of radiogenic helium (He) in the aged material. Abstract : The high alpha-activity of plutonium dioxide (PuO2 ) results in significant ingrowth of radiogenic helium (He) in the aged material. To safely store/dispose PuO2 or use in applications such as space exploration, the impact of He accumulation needs to be understood. In this work, defect energies obtained using a density functional theory (DFT) + U + D3 scheme are used in a point defect model constructed for PuO2 to predict the method of He incorporation within the PuO2 lattice. The simulations predict that the preferred incorporation site for He in PuO2 is a plutonium vacancy, however, the point defect model indicates that helium will be accommodated as an interstitial irrespective of He concentration and across a wide stoichiometric range. By considering the charge imbalance that arises due to incorporation of Am 3+ ions it is shown that He accommodation in oxygen vacancy sites will dominate in PuO2− x as the material ages.